A mixed method approach to validating barriers to safety incentives implementation in the Nigerian construction industry - Ogundipe, Kunle Elizah; Aigbavboa, Clinton Ohis; Ogunbayo, Babatunde Fatai (Frontiers in Built Environment, 2025)
The position of safety incentives in the construction industry emerged from the demands to align employees with organisational performance-related goals, improve workplace safety practices, and share risk between clients and contractors. This study identifies and validates barriers to safety incentives implementation in the construction industry using an exploratory sequential mixed-methods design. The study addresses this critical gap by delving into construction firms’ challenges in implementing safety incentives. Twenty-three of thirty-two identified barriers to implementing safety incentives from the literature review were validated through a Delphi survey using expert panellists’ opinions. This is followed by obtaining quantitative data from construction professionals (architects, builders, engineers, and quantity surveyors) using a structured questionnaire in Lagos, Nigeria, through a simple random sampling technique. Descriptive and exploratory factor analysis was conducted on the retrieved data and Cronbach’s alpha test to determine data reliability and interrelatedness. The twenty-three validated barriers to safety incentives implementation in the construction industry were clustered into six factors: discrepancies in the incentive rewards process, lack of incentive budget planning, conflicting incentive performance indicators, absence of a national safety incentive policy, construction firms’ governance systems, and lack of automation in the incentive implementation process. The practical implication of this study is to provide a better understanding of national safety policy, key performance indicators, and scheme selection approaches supporting the implementation of safety incentives. The study provides actionable recommendations for construction stakeholders, government agencies, professional institutions, safety managers, and policymakers to prioritise incentive budget planning, incentive reward approaches, automation processes, and key performance indicators to improve safety incentive implementation. The study concluded by calling on construction stakeholders’ commitment to developing safety incentives and performance goals that will not conflict with health and safety practices or create workplace tension among workers.